MANAJEMEN PERSEDIAAN BAHAN BAKU KOPI BUBUK PADA UKM SIDOLE 986 DI KOTA PALU - Iswah Marina; Dafina Howara; Sulmi Sulmi (Jurnal Pembangunan Agribisnis (Journal of Agribusiness Development), 2022)
SMEs Sidole 986 Coffe Powder UKM Sidole 986 is one of the businesses engaged in the agro-industry that utilizes Robusta coffe bean as the main raw material. This study aims to determine how much economic raw material purchases (EOQ) for raw material supplies in the SMEs Sidole 986, to find out how much safety stock is in the, SMEs Sidole 986 to find out when is the right time for the SMEs Sidole 986 to do so. reorder (ROP) for raw material inventory, and to find out the total cost of raw material inventory (TIC) in the SMEs Sidole 986. The results of this study indicate that the management of raw material inventory in the SMEs Sidole 986 using the (Economic Order Quantity) method in July-December 2021 an average of 42,02 kg. Safety stock of raw materials which is always available at SME Sidole 986 is 22,84 kg. Reorder Points that must be made by the SMEs Sidole 986 in July-December 2021 an average of 127,12 kg. The total cost of the raw material inventory coffe powder carried out in the SMEs Sidole 986 is an average of Rp. 75.824,74.